Experimental determination of the ventilation pressure thermal drop effect on the air flows in the inclined mine workings - Lev Levin; Evgeniy Kuzminykh; Sergei Zhikharev (Frontiers in Mechanical Engineering, 2025)
The increasing use of mechanized facilities in underground mining operations, including conveyor systems, diesel and electric equipment, and rail transport, is driving the expansion into new mineral reserves, often accessed through inclined mine workings. Many of these workings are located in moderately pitched deposits, where mining conditions present particular safety challenges. Among the most critical risks is fire, which can significantly alter airflow patterns and disrupt mine ventilation systems. While fire-induced airflow and temperature distribution have been studied extensively in buildings and road tunnels, similar investigations for underground mine workings remain scarce and are typically limited to simplified one-dimensional models. However, the results from studies on buildings and tunnels cannot be directly applied to mine environments due to significant differences in geometry and ventilation systems. This study investigates the effects of ventilation pressure drops on air velocity and temperature field heterogeneity in inclined mine workings with positive and negative inclination angles. We experimentally determine the relationship between mass airflow rate changes in mine workings with inclination angles ranging from 12° to −15° and a fixed heat source power. For the first time, we examined asymmetrical changes in airflow in inclined mine workings for positive and negative inclination angles. A theoretical justification for the observed experimental phenomenon is provided. Additionally, we identify the critical power range of the heat source at which airflow choking and direction reversal occur in workings with descending ventilation, providing valuable insights for improving mine ventilation safety during fire scenarios.